Tetra-Uranium Fluoride Electrowinning by Electro-Electrodialysis Cell (Eed) - Cifuentes-Molina, G; Pino-Lopez, E; Calderon-Espinoza, C; Calderon-Espinoza, C; Garrido-Moreno, B (Elsevier B.V., 2022)
This work presents a novel electro-electrodialysis (EED) system for laboratory-scale uranium electrowinning based on a simple process of reactive electrodialysis of solutions of uranium (VI) oxide (UO3) dissolved in aqueous hydrofluoric acid (HF), leading to the formation of deposits of uranium tetrafluoride (UF4). For stainless steel cathodes, the best operating conditions for a concentration of 25 g/L for uranium were i = 40 A/m2, T = 40 °C and 18 L/h electrolyte recirculation flowrate. The specific energy consumption (W) and current efficiency (ρ) for tetra uranium fluoride electrowinning was 4500 kWh/kg and 10.15%. When the cathodic metal was changed from stainless steel to aluminium, seeking to optimize the system, improved values of W and ρ were achieved (645 kWh/kg and 68%, respectively). In the EED cells, the release of gaseous hydrogen is significantly lower for aluminum, due to its lower exchange current density (i0), with a magnitude of 10-7 A/m2. On the contrary, a considerable release of gaseous hydrogen is observed when the stainless-steel cathode is used, mainly due to the H+/H2 reaction being catalysed by the stainless steel, inducing an increase in the acid consumption rate, devoting most of the energy consumed by the system in the proton reduction reaction. Polarization cathodic curves indicate that uranium has an estimate resting potential close to that of aluminium, which is −0.89 V. Finally, by chemical analysis (X-ray mass diffraction), UF4 and hydrated UF4 were identified as the main components of the electrodeposited product. © 2021